Metal‐Loaded Dielectric Resonator Metasurfaces for Radiative Cooling. Issue 20 (11th August 2017) - Zou, Chengjun; Ren, Guanghui; Hossain, Md Muntasir; Nirantar, Shruti; Withayachumnankul, Withawat; Ahmed, Taimur; Bhaskaran, Madhu; Sriram, Sharath; Gu, Min; Fumeaux, Christophe
Abstract: Tailoring emissivity and absorptivity of structured material surfaces to match atmospheric transmission spectral windows can lead to radiative cooling that consumes no external energy. Recent advances in nanofabrication technology have facilitated progress in the realization of structured metasurfaces. In particular, subwavelength dielectric resonator metasurface supporting various resonance modes can be efficient absorbers. Here, such metasurfaces are proposed and experimentally demonstrated enhanced by metal loading to obtain strong broadband thermal emission over a wide angle at mid‐infrared frequencies. This concept results in passive cooling devices that can lower temperature by 10 °C below ambient temperature. Importantly, the utilization of standard constituent materials and processes lead to scalable fabrication compatible with silicon photonics integration, which will enable effective and energy‐efficient applications in passive cooling and thermodynamic control. Abstract : A metal‐loaded dielectric resonator metasurface is proposed and experimentally demonstrated. The structure achieves strong broadband selective thermal emission over a wide angle at mid‐infrared frequencies. This concept results in passive cooling devices that can lower temperature by 10 °C below ambient temperature.